Factors Affecting Chinese English as a Foreign Language Teachers' Technology Acceptance: A Qualitative Study. (March 2019) - Huang, Fang; Teo, Timothy; Zhou, Mingming
This article explores Chinese English as a Foreign Language (EFL) teachers' attitudes toward technology use and the factors that influence their technology acceptance. A qualitative study was conducted with data obtained from semistructured, in-depth interviews of 14 university teachers from six provinces. The interview data revealed that Chinese EFL teachers generally maintained a positive attitude toward technology use in teaching. Facilitating conditions driven by modernization, perceived usefulness, subjective norm, and technology mania are major factors influencing their technology acceptance. It is worth noticing that the degree of reliance on technology varied in terms of age and experience. Overall, the findings were consistent with previous studies, while leading to a broader and deeper understanding of technology acceptance theories by analyzing contextual and cultural phenomenon in China. Implications for future research and suggestions to improve Continuing Professional Development were provided in order to promote technology integration among Chinese teachers.